Общий знаменатель:
[tex] {c}^{2} (a + c)[/tex]
Приведём дроби
[tex] \frac{8a}{ {c}^{2} } = \frac{8a(a + c)}{ {c}^{2}(a + c) } = \frac{8 {a}^{2} + 8ac}{ {c}^{2}(a + c) } [/tex]
[tex] \frac{5a - c}{a + c} = \frac{ {c}^{2}(5a - c) }{ {c}^{2} (a + c)} = \frac{5a {c}^{2} - {c}^{3} }{ {c}^{2} (a + c)} [/tex]
[tex] \frac{9}{c} = \frac{9c(a + c)}{ {c}^{2}(a + c) } = \frac{9ac + 9 {c}^{2} }{ {c}^{2} (a + c)} [/tex]
Верные ответы: 1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Общий знаменатель:
[tex] {c}^{2} (a + c)[/tex]
Приведём дроби
[tex] \frac{8a}{ {c}^{2} } = \frac{8a(a + c)}{ {c}^{2}(a + c) } = \frac{8 {a}^{2} + 8ac}{ {c}^{2}(a + c) } [/tex]
[tex] \frac{5a - c}{a + c} = \frac{ {c}^{2}(5a - c) }{ {c}^{2} (a + c)} = \frac{5a {c}^{2} - {c}^{3} }{ {c}^{2} (a + c)} [/tex]
[tex] \frac{9}{c} = \frac{9c(a + c)}{ {c}^{2}(a + c) } = \frac{9ac + 9 {c}^{2} }{ {c}^{2} (a + c)} [/tex]
Верные ответы: 1